Identifying and adapting interventions to reduce documentation burden and improve nurses' efficiency in using electronic health record systems (The IDEA Study): protocol for a mixed methods study - Gillian Strudwick; Lianne Jeffs; Jessica Kemp; Lydia Sequeira; Brian Lo; Nelson Shen; Petroiya Paterson; Noelle Coombe; Lily Yang; Kara Ronald; Wei Wang; Sonia Pagliaroli; et al. (BMC, 2022)
Abstract Background Although EHR systems have become a critical part of clinical care, nurses are experiencing a growing burden due to documentation requirements, taking time away from other important clinical activities. There is a need to address the inefficiencies and challenges that nurses face when documenting in and using EHRs. The objective of this study is to engage nurses in generating ideas on how organizations can support and optimize nurses' experiences with their EHR systems, thereby improving efficiency and reducing EHR-related burden. This work will ensure the identified solutions are grounded in nurses' perspectives and experiences and will address their specific EHR-related needs. Methods This mixed methods study will consist of three phases. Phase 1 will evaluate the accuracy of the EHR system's analytics platform in capturing how nurses utilize the system in real-time for tasks such as documentation, chart review, and medication reconciliation. Phase 2 consists of a retrospective analysis of the nursing-specific analytics platform and focus groups with nurses to understand and contextualize their usage patterns. These focus groups will also be used to identify areas for improvement in the utilization of the EHR. Phase 3 will include focus groups with nurses to generate and adapt potential interventions to address the areas for improvement and assess the perceived relevance, feasibility, and impact of the potential interventions. Discussion This work will generate insights on addressing nurses' EHR-related burden and burnout. By understanding and contextualizing inefficiencies and current practices, opportunities to improve EHR systems for nursing professional practice will be identified. The study findings will inform the co-design and implementation of interventions that will support adoption and impact. Future work will include the evaluation of the developed interventions, and research on scaling and disseminating the interventions for use in different organizations, EHR systems, and jurisdictions in Canada.